Development communication for collaborative governance: Empowering women farmers in food independent villages - Purwanto, Eko; Shahreza, Mirza; Rahmah, Ade (International Journal of Innovative Research and Scientific Studies, 2025)
Tangerang Regency faces food security challenges due to high poverty rates and nutritional insecurity, particularly in rural areas such as Sodong Village, a pilot site for the Food Independent Village Program. Despite its considerable agricultural potential, the village encounters obstacles including limited resources, low community participation, and suboptimal communication strategies in the empowerment of Women Farmers Groups (Kelompok Wanita Tani or KWT in Bahasa Indonesia). This study aims to analyze the collaborative governance model in KWT empowerment, evaluate its impact on food security and village socio-economic welfare, and identify development communication strategies that can strengthen the participation and technical capacity of KWT members. A qualitative approach with a case study design was employed, with data collection techniques including in-depth interviews, participant observation, and document analysis. The study in Sodong Village, Tangerang Regency, shows that cross-actor involvement—including the village government, technical agencies, KWT, the community, and the private sector—plays a crucial role in shaping participatory and inclusive governance in the implementation of the Food Independent Village Program. In this context, KWT has transformed into an agent of social change, contributing to increased consumption of nutritious food, higher household income, and strengthened women's roles in local decision-making processes. Identified development communication strategies include interpersonal, digital, institutional, educational, and multi-sectoral communication, which collectively create a dialogical and collaborative ecosystem to foster active participation and enhance the technical capacity of KWT members.